BUILDING EARLY CHILDHOOD CHARACTER THROUGH MEANINGFUL PLAY ACTIVITIES: A THEORETICAL STUDY: MEMBANGUN KARAKTER ANAK USIA DINI MELALUI KEGIATAN BERMAIN BERMAKNA: SUATU KAJIAN TEORETIS - Anis Soleha; Intan Putri Aulia (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2025)
Character education for early childhood is still not fully integrated into play activities in many early childhood education institutions, even though play is an approach that aligns with children's developmental stages. The method applied in this study is a literature study or library research method. The results show that meaningful play activities can foster character values ​​such as honesty, responsibility, empathy, and collaboration through direct experience in social interactions. Children learn to understand game rules, imitate positive behavior from friends and educators, and develop moral awareness when participating in group play. Furthermore, the involvement of educators in designing relevant games and providing role models, along with family support at home, strengthens the process of internalizing character values. The conclusion of this study confirms that meaningful play is an effective and natural means for character formation in early childhood, and therefore needs to be systematically integrated into the early childhood curriculum to ensure the process of character development is sustainable and aligned with children's developmental needs.